Using A Whitesmoke Checker as A Technology To Enhance English Writing Classroom - siswandi siswandi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This paper is to demonstrate how technology enhances writing in the classroom. The word processors should be part of every classroom to support students, especially those who have motor skills issues, because it indicated that technology allows students to enhance their writing by adding more precise detail into their writing pieces and it initiates self-revisions. Moreover, the use of technology to support the learning and understanding of language to students is essential because writing students tend to need proof of skills that they are learning. Literacy is learned through acquisition, but additional supports may be needed in order to attain the explicit knowledge, therefore technology may be an appropriate strategy to support struggling writers. Literacy development does not evolve within the course of a day. It evolves throughout the course of an individual life time.